(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes most used architectural words with specialized texts. The intention of this research is to inspire a discussion about the changes in architecture terminology with the revolution in communication and representation forms as a result of digitalisation.Research on technical vocabulary has shown a significant underestimation of the role played by technical vocabulary in specialized texts and lack of information about how technical vocabulary relates to other types of vocabulary. Also in this article has shown a study of the technical vocabulary in an architecture text and the technical vocabulary in an applied linguistics texts